THE AFRICAN WOMEN’S POWERS PROMOTION IN MALE DOMINATED SOCIETIES IN CHINUA ACHEBE’S THINGS FALL APART, NGUGI WA THIONG’O’S PETALS OF BLOOD AND PETER ABRAHAM’S A WREATH FOR UDOMO - HOUNDJO, THÉOPHILE; DJOSSOU AGBOADANNON, Koumagnon Alfred (My University, 2022)
The present paper examines the African women’s powers promotion system as described in three inspiring novels by male writers. It highlights the real positions of women in African societies far from their common degrading roles wrongly assigned in some male writings. This is done through a critical analysis of the novels, Things Fall Apart (1958), Petals of Blood (1986) and A Wreath for Udomo (1956), all classics. In these novels, women are portrayed in some ways, so that self-aware of their powers, knowledgeable persons, skilled and spiritually ordained to have their words reckoned in their community with no haughtiness. Based on the natural powers of women in African societies depicted in the novels, the paper tries to demonstrate the pivotal roles of women, by the help of theories like postcolonial, feminism and psychoanalysis, contrary to the general lens women have been heard, seen and perceived.
Keywords: Women; powers; education; domination; empowerment.